Delovni čas in letni dopust - Senčur Peček, Darja (Podjetje in delo, 2023)
When regulating working hours and annual leave, employers and employees are obliged to act in accordance with applicable legislation and collective agreements, which must be interpreted in accordance with the international and EU acts that were their basis. In the recent period, several important decisions of the Court of Justice of the European Union (CJEU) regarding the interpretation of Directive 2003/88/EC and the EU Charter, as well as decisions of the Supreme Court of the Republic of Slovenia, were adopted, in which the views of the CJEU were taken into account. Due to some decisions of the CJEU, the implementation of new directives and new challenges related to working time, changes to Slovenian labour legislation are also necessary. In this paper, some issues of working time and annual leave are discussed, mainly in the light of the more recent case law of the CJEU and the Supreme Court of the Republic of Slovenia and the proposal for amendments to the Employment Relationships Act (ZDR-1).
Keywords: delovni čas; Delovno pravo; kolektivne pogodbe; letni dopust; počitek; polni delovni čas; Sodišče EU; zakonodaja